1990
DOI: 10.1111/j.1365-3083.1990.tb02756.x
|View full text |Cite
|
Sign up to set email alerts
|

apo‐SAA1/apo‐SAA2 Isotype Ratios during Casein‐ and Amyloid‐Enhancing‐Factor‐Induced Secondary Amyloidosis in A/J and C57BL/6J Mice

Abstract: A/J mice are resistant while C57BL/6J are susceptible to casein-induced secondary amyloidosis. One mechanism responsible for this phenotypic expression of resistance/susceptibility was shown to operate at the level of production of the 'amyloid-enhancing factor' (AEF). AEF and processing of the apo-SAA protein appear almost concomitantly during amyloidogenesis. In order to determine if AEF played a role in the processing of the apo-SAA protein, three major parameters (apo-SAA1/apo-SAA2 ratios, level of AEF, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
4
6
0
Order By: Relevance
“…As WT mice with chronic inflammation become amyloidotic, the SAA1:SAA2 concentration ratio increases sharply, and the total circulating SAA value falls modestly, consistent with selective sequestration of SAA2 into amyloid (32,33). Our present finding of a dramatic fall of SAA2 values in all of the transgenic mice as amyloid was being deposited was similarly consistent with such sequestration.…”
Section: Discussionsupporting
confidence: 77%
“…As WT mice with chronic inflammation become amyloidotic, the SAA1:SAA2 concentration ratio increases sharply, and the total circulating SAA value falls modestly, consistent with selective sequestration of SAA2 into amyloid (32,33). Our present finding of a dramatic fall of SAA2 values in all of the transgenic mice as amyloid was being deposited was similarly consistent with such sequestration.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, our AEF-treated control group showed no differences from the PBS-treated control mice (group 1) with respect to any of the APR studied (data not shown), indicating that AEF per se is non-inflammatory and that the induction of the acute phase response in our experiments was due solely to AgN03 administration. This is in agreement with other reports that AEF does not induce an acute inflammatory response [25,26]. + rmIL-lra (W) (as described in Table 1).…”
Section: Resultssupporting
confidence: 94%
“…Some evidence for SAA deposition in tissues of amyloidotie mice was demonstrated in several earlier studies. First, it was found that during amyloid deposition the level of apo SAA2 (one of two SAA isomers) was decreased in the serum of amyloidotie mice without a corresponding reduction in hepatic SAAi mRNA level [31,32]. Since no detectable synthesis of SAA was found in spleen and there was amino acid sequence identity between apo SAA; and protein AA [33], It was suggested that SAA2 is selectively removed from circulation, deposited in tissues and then it degraded to protein AA [31].…”
Section: Discussionmentioning
confidence: 99%